2021
DOI: 10.3390/ijms222111874
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Pathology in Myotonic Dystrophy Type 1

Abstract: Myotonic dystrophy type 1 (DM1), the most common muscular dystrophy affecting adults and children, is a multi-systemic disorder affecting skeletal, cardiac, and smooth muscles as well as neurologic, endocrine and other systems. This review is on the cardiac pathology associated with DM1. The heart is one of the primary organs affected in DM1. Cardiac conduction defects are seen in up to 75% of adult DM1 cases and sudden death due to cardiac arrhythmias is one of the most common causes of death in DM1. Unfortun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 128 publications
1
19
0
Order By: Relevance
“…As a result, these active fixation leads should be implanted cautiously. Anatomic variations, such as multilobed or a thin-walled atrial appendage, fatty infiltration of the myocardium due to myotonic dystrophy, ischemic and dilated cardiomyopathy, are variables that increase the likelihood of atrial perforation ( 10 , 11 , 13 , 15 , 20 , 23 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, these active fixation leads should be implanted cautiously. Anatomic variations, such as multilobed or a thin-walled atrial appendage, fatty infiltration of the myocardium due to myotonic dystrophy, ischemic and dilated cardiomyopathy, are variables that increase the likelihood of atrial perforation ( 10 , 11 , 13 , 15 , 20 , 23 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, heart diseases are a major cause of sudden death in patients with DM1. First-degree atrioventricular block is the most common conduction disorder and other defects, including bundle branch blocks and prolongation of the QRS interval on surface electrocardiogram (ECG), are frequent with increased disease duration or severity [ 108 ]. Cardiac histopathology features fibrosis, fatty infiltration, and cardiomyocyte hypertrophy.…”
Section: Systemic Therapy For Dm1 With Naked Asosmentioning
confidence: 99%
“…They include the CRISPR/Cas approach [ 5 , 6 ], as well as the application of small molecules, restoring MBNL1 and CUGBP1 activities or correcting splicing via other RNA-binding proteins [ 7 , 8 , 9 , 10 ]. Although indirectly, several review papers referred to the use of AONs as a potential therapy for DM1 [ 5 , 7 , 8 , 10 , 11 , 12 ].…”
Section: Figurementioning
confidence: 99%
“…While the first attempt to reduce DM1 pathology with the DMPK1 -specific AON in a clinical trial for adult DM1 was not successful due to the low penetration of AON in skeletal muscle, studies on the improvement of this approach continue. More importantly, preclinical studies in DM1 showed that AONs were beneficial not only for the skeletal muscle pathology, but that they could also reduce cognitive defects and reverse cardiac phenotypes [ 12 , 14 , 15 ]. As described in Dr. Mahadevan’s review, which focused on cardiac pathology in DM [ 12 ], the application of the DMPK -specific AON in the preclinical study using a tet-inducible DM1 mouse model, expressing the 3′UTR of DMPK with 200 CUG repeats, reduced skeletal and cardiac muscle deficiencies [ 12 , 15 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation